Improvement of Nicotine Removal and Ethanol Fermentability From Tobacco Stalk by Integration of Dilute Sulfuric Acid Presoak and Instant Catapult Steam Explosion Pretreatment - Zhang, Hongsen; Fu, Chenqing; Ren, Tianbao; Xie, Hui; Mao, Guotao; Wang, Zhimin; Wang, Fengqin; Song, Andong (Frontiers in Bioengineering and Biotechnology, 2021)
The nicotine from tobacco stalk showed obvious inhibitory effect on the activity of cellulase and fermentability of microorganisms, which seriously hindering the utilization of tobacco stalk. Dilute sulfuric acid presoak of tobacco stalk was used to enhance the performance of instant catapult steam explosion (ICSE) for tobacco stalk pretreatment. The presoak was beneficial to broke the recalcitrant structure of tobacco stalk, reduce nicotine content to relieve the inhibition on activity of cellulase and metabolism of microorganisms, and promote the performance of enzymatic hydrolysis and ethanol fermentation. The optimized 0.8% sulfuric acid (w/w) presoak integrated ICSE pretreatment could remove 85.54% nicotine from tobacco stalk, meanwhile the total sugar concentration from enzymatic hydrolysis of pretreated tobacco stalk increased from 33.40 to 53.81 g/L (the ratio of dry tobacco stalk to water was 1:8, w/w), ethanol concentration increased 103.36% that from 5.95 to 12.10 g/L in flask, compared with separate ICSE pretreatment. Finally, the ethanol concentration achieved to the highest 23.53 g/L in 5 L fermenter by increasing the solid loading of tobacco stalk in the enzymatic hydrolysis process (the ratio of dry tobacco stalk to water was 1:4, w/w), the ethanol yield from the glucose of tobacco stalk hydrolysate achieved to 71.40%, which achieved the expect purpose of efficient utilization of discarded tobacco stalk.